Combining ability, floral biology, and seed producibility of promising cytoplasmic male-sterile (CMS) lines for hybrid rice development - Victoriano V. Casco; Rosemarie T. Tapic; Jerwin R. Undan; Anna Ma. Lourdes S. Latonio; Roel R. Suralta; Norvie L. Manigbas (CABI Agriculture and Bioscience)
Abstract Background A combining ability analysis is a useful tool of plant breeders in screening and identifying promising parental lines with high potential for developing competitive rice hybrids. Also, one important factor that strongly determines the suitability of commercial utilization of hybrid rice parental lines is their extent of seed producibility. Methods In this study, the combining ability, floral biology and seed producibility of cytoplasmic male sterile (CMS) lines were investigated to identify good combiners with good seed production potential. The Line × Tester analysis was used to determine the general combining abilities (GCA) of hybrid rice parental lines, and Specific Combining Abilities (SCA) of the different hybrid combinations. A correlation analysis was also done to determine floral traits that influence the outcrossing rate of the CMS lines. There were 4 CMS lines, 6 restorer lines, 24 hybrid combinations and 1 check variety in a randomized complete block Design (RCBD) with 3 replicates. Results Results indicated that CMS lines IR79128B and IR102758B were good combiners and the most promising restorer lines were D2031-7-1-2R, Hanareumbyeo 2, and XTR036-54-10R. Based on specific combining ability test, the most promising combination was entry 10 (IR58025A/D2013-7-1-2R). It has the highest yield of 7496 kg ha−1, a high positive SCA score of 570.54, and highest standard heterosis of 12.9%. Based on floral traits, IR79128B was the most promising with a high positive GCA score of 186.93, panicle exertion rate of 74.8%, and a high outcrossing rate of 51%. There was a significant positive association between outcrossing rate, duration of floral opening, panicle exertion rate, and general combining ability. Conclusion The floral traits found to be significantly associated with outcrossing rate are useful selection criteria not only for identifying economically usable CMS lines but also for developing new and promising parental lines and hybrids. These CMS lines do not only give heterotic combinations but are also commercially producible, the two most important factors to the success of any hybrid rice breeding program.